'Spare' Luteinizing Hormone Receptors: Facts and Fiction. (April 2018) - Casarini, Livio; Santi, Daniele; Simoni, Manuela; Potì, Francesco
Abstract : It is common opinion that maximal activation of luteinizing hormone (LH)-dependent steroidogenic signal occurs at <1% of human LH/choriogonadotropin (hCG) receptor (LHCGR) occupancy. This effect would be a consequence of an excess of receptors expressed on the surface of theca cells, resulting in a pool of LHCGRs remaining unbound (spare). This concept was borrowed from historical pharmacological studies, when discrepancies between ligand–receptor binding and dose–response curves of cAMP were evaluated by treating mouse or rat Leydig cells with hCG in vitro . Recent findings demonstrated the specificity of LH- and hCG-dependent effects, receptor heterodimerization, and differing behaviors of rodent versus human gonadotropin-responsive cells, which may help to revise the 'spare' LHCGRs concept applied to human ovarian physiology and assisted reproduction. Highlights: The existence of 'spare' LH/hCG receptors (LHCGRs) is a long-standing concept currently used to explain unclear aspects of ovarian physiology. Accordingly, maximal steroid synthesis would be triggered by the activation of <1% of occupied LHCGRs. This concept, arisen from pioneering in vitro experiments using rodent Leydig cells stimulated by hCG, is challenged by recent advancements, that is, different LH- versus hCG-mediated signaling, specific rodent Leydig versus human ovarian cell response to hormones, and heterodimerization between gonadotropin receptors and its role in vivo . The finding of FSHR–LHCGR heterodimers in vitro may provide a promising alternative to the 'spare' receptors concept for explaining LHCGR-dependent androgenic signals at the early antral follicular stage in vivo . An up-to-date model of folliculogenesis re-draws the ovarian physiology of the antral stage, highlighting the relevance of FSHR–LHCGR heterodimers and overshadowing the involvement of 'spare' LHCGRs. While 'spare' LHCGRs could be confirmed by noncompetitive antagonists, bivalent ligands might be a promising tool for detecting FSHR–LHCGR heterodimers in human tissues in the next years.